Neoliberalization, Universities and the Public Intellectual Species, Gender and Class and the Production of Knowledge - Fraser, Heather; Taylor, Nik.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
This book employs an an intersectional feminist approach to highlight how research and teaching agendas are being skewed by commercialized, corporatized and commodified values and assumptions implicit in the neoliberalization of the academy. The authors combine 50 years of academic experience and focus on species, gender and class as they document the hazardous consequences of seeing people as instruments and knowledge as a form of capital. Personal-political examples are provided to illustrate some of the challenges but also opportunities facing activist scholars trying to resist neoliberalism. Heartfelt, frank, and unashamedly emotional, the book is a rallying cry for academics to defend their role as public intellectuals, to work together with communities, including those most negatively affected by neoliberalism and the corportatization of knowledge. .
Chapter 1. The University Goes to Market: The Infiltration of Neoliberalism -- Chapter 2. Producing Marginalized Knowledge: Privilege and Oppression on the Basis of Species, Class and Gender -- Chapter 3. Connecting With Others at the Margins: Researching Women, Companion Animals, Love and Loss -- Chapter 4. Researching Marginalised issues, Policies and Programs: Companion Animals, Same Sex Abuse and Housing -- Chapter 5. Living on the Margins: Producing 'Evidence' with 'Feral' Drug Users -- Chapter 6. Looking Ahead, Strategies for Resistance and Change -- Conclusion: Where to From Here?.
Keywords: Education; Philosophy of nature; Educational sociology; Higher education; Education -- Philosophy; Gender identity in education; Sociology; Education and sociology; Sociology, Educational; Sex (Psychology).; Gender expression; Gender identity; Education; Sociology of Education; Higher Education; Gender and Education; Educational Philosophy; Philosophy of Nature; Gender Studies; Electronic books